Political participation of women in Iran after 1979 Islamic Revolution - Shojaei, Seyedeh Nosrat (2012)
This research describes the political participation of women in Iran after the 1979 Islamic Revolution. Research objectives were achieved by respondents answering three questions: 1) How do women politicians describe their experiences about the cultural obstacles to women in Iranian politics? 2) From their perspective, what factors have they perceived as structural obstacles to women in the politics of Iran? 3) What lessons can women draw from their experiences which might suggest ways to increase the proportion of women in similar positions? The research employs a qualitative case study method and the primary data was collected mainly through in-depth interviews with thirteen informants using a purposive technique. The study informants were chosen from Iranian women who were at least members of a political party and with more than 10 years political experience. Interviews were tape-recorded and transcribed, and field notes have been taken to record the data. A qualitative analysis was employed to transform the data into a workable form. Trustworthiness and ethical practice were adhered to during the whole process. The research findings showed that female Iranian politicians agree that they face cultural and structural obstacles to their entrance into top political positions. The data revealed that gender stereotypes and a patriarchal culture act as cultural obstacles, while inadequate educational and financial resources are structural barriers to Iranian women in frontline politics. Several conclusions can be drawn from this research. This study found agreement among the informants that women faced cultural and structural barriers in their efforts to enter into top political positions in Iran. A key finding of this study was how the level of education and occupation increase women’s mobility, making them more confident regarding major political decisions. According to this view, the more women are educated and employed gainfully,the more involved they are in power decision-making. Therefore, taken together,educational and financial resources appear to contribute more effectively to boost women’s self-reliance and enhance their role in Iranian politics. The study findings also strongly support the gender differences theory in terms of cultural perspective. This emphasizes that the low level of political participation by women is influenced by three factors namely biological, situational and socialization. The main argument for these factors is that women’s participation in politics is influenced by gender and culture ideology,which is in turn, socially and culturally determined. According to this belief,women are inculcated that politics is the domain of men only and incorporate it into their self-conceptions. From these factors, cultural norms such as gender stereotypes which are the result of patriarchy, have preserved the definition of politics as being men’s work. As the data shows, gender differences were reflected in informants’ experiences. They had observed gender stereotypes as well as patriarchal and male dominance during their political activities. Therefore, these factors act as cultural obstacles to women’s presence in the politics of Iran. This study furthermore promoted a better theoretical understanding and knowledge in the area of political participation of women; and thus also contributes to women studies generally. Finally, some implications of the study were presented.